Electromagnetic Test Environments Analysis for EMI Measurements - Dwi Mandaris; Hutomo Wahyu Nugroho; Yoppy Yoppy; Tyas Ari Wahyu; Elvina Trivida; Yudhistira Yudhistira (LIPI Press, Anggota IKAPI, 2021)
This paper presents an analysis and review of different electromagnetic (EM) test environments for Electromagnetic Interference (EMI) measurements to verify its advantages or disadvantages and to obtain the correlation between those environments, namely: semi-anechoic chamber (SAC), fully anechoic room (FAR), classical reverberation chamber (RC) and vibrating intrinsic reverberation chamber (VIRC). The first analysis is based on literature studies from previous research by analyzing four key parameters: power-to-electric field ratio, the frequency range, equipment under test (EUT) size, and on-site measurement applicability. In order to verify their correlation, further investigation was done by radiated emission (RE) measurement of dummy EUT, simple monopole, in those environments. The literature study concluded that each test environment has advantages and drawbacks concerning some aforementioned evaluation. The existing SAC environment showed more established technique, but expensive and time-consuming. However, despite the small limitation on susceptibility and dwell time, RC, in particular VIRC, delivers potential and promising technique, with statistically good E-field uniformity, more time-efficient and on-site measurement applicability. The radiated emission simulation and measurement results of monopole antenna confirmed their correlation and the E-field strength graph showed a considerably similar pattern, except for frequency range 1.6 to 2 GHz where null radiation pattern occurs for some azimuth angle.